1997
DOI: 10.7748/ns1997.02.11.22.33.c2442
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and GPs’ views of the nurse prescribers’ formulary

Abstract: This article presents the findings from the evaluation of nurse prescribing, undertaken in eight demonstration sites since October 1994. The authors examine in particular the nurses' prescribing behaviour and the type of items nurses and GPs would like to see added to the formulary. The opportunities for prescribing and the limitations of the formulary for health visitors and practice nurses are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Nurses with an HV or DN qualification at each demonstration site undertook the necessary training prior to the commencement of nurse prescribing on 3 October 1994. The findings relating to the prescribing aspects of the study have been reported elsewhere ( Luker et al 1997a , 1997b, 1997c, 1997d).…”
Section: The Gp–patient Relationship and Nurse–patient Relationshipsupporting
confidence: 70%
“…Nurses with an HV or DN qualification at each demonstration site undertook the necessary training prior to the commencement of nurse prescribing on 3 October 1994. The findings relating to the prescribing aspects of the study have been reported elsewhere ( Luker et al 1997a , 1997b, 1997c, 1997d).…”
Section: The Gp–patient Relationship and Nurse–patient Relationshipsupporting
confidence: 70%
“…prescription pad) to use the knowledge and skills aquired. This lack of opportunity to rehearse prescribing once qualified, has been reported previously in the CPNP literature as slowing down the development of confidence to prescribe with increased confidence associated with higher prescribing rates (Luker, et al, ; Sodha, McLaughlin, Williams, & Dhillon, ). Motivation to prescribe was influenced by cost to the NHS, with CPNPs using their prescribing skills to recommend over‐the‐counter (OTC) medicines to patients with minor illnesses.…”
Section: Discussionmentioning
confidence: 80%
“…Before the study reported here, research into nurse prescribing (for example, see Luker et al 6 7 and Otway8) was largely confined to descriptive accounts of views of district nurses and heath visitors trained to prescribe a few medicines from a nurse prescribers’ formulary in the introductory first phase of nurse prescribing between 1996 and 2002. No previous research directly evaluated the quality or safety of nurses’ prescribing practice.…”
mentioning
confidence: 99%